Bovine fluorosis and its effects on essential minerals, haemogram and biochemical status in the fluoride endemic South-West Punjab of India - SINGH, S T; DUA, K; GUPTA, D K; RANDHAWA, S S; BANSAL, B K (The Indian Journal of Animal Sciences, 2017)
The present study was undertaken to assess prevalence of fluorosis and its effects on essential mineral and haemato-biochemical status in dairy animals from the fluoride endemic Mansa and Fazilka districts of the South- West Punjab, India. A base line survey was carried out in which blocks of the selected districts were taken as a stratum and from each stratum, the buffaloes and cattle were selected randomly. Blood samples of the selected animals were analysed for plasma Ca, Pi, Mg, Cu, Mo, Zn, Fe, Mn, alkaline phosphatase, Hb, PCV and TEC. The fluoride contents of 35.6 and 9.9% drinking water samples from Mansa (1.46±0.17 ppm, n=112) and Fazilka (1.18±0.36 ppm, n=91) district, respectively, were higher than the permissible limit of 1.5 ppm. The prevalence of fluorosis (plasma F > 0.10 μg/ml) in Mansa district was 95.3% in buffaloes (0.26±0.01 μg/ml, n=261) and 100.0% in cattle (0.31±0.02 μg/ml, n=35); while in Fazilka district, the prevalence was 92.0% in buffaloes (0.17±0.01 μg/ml, n=112) and 95.7% in cattle (0.21±0.01 μg/ml, n=118). The fluorotic buffaloes and cattle had significantly lower plasma Pi, Zn, Mn, PCV, TEC, and significantly higher plasma Mo and alkaline phosphatase activity. Plasma Ca, Mg, Cu, Fe and Mn, and Hb concentrations did not vary between the fluorotic and normal animals. It can be conclude that fluorosis is widely prevalent, and is causing essential mineral imbalances and lowering of haemogram in the dairy animals in the Mansa and Fazilka districts of the South-West Punjab of India.